Efektivitas Kegiatan Ekstrakurikuler Palang Merah Remaja Dalam Membentuk Karakter Peduli Sosial Pada Peserta Didik Kelas XI di SMA N Colomadu - Miftah Tedy gautama, Miftah Tedy Gautama; FARIDA, AMA; Sutoyo, Sutoyo (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2024)
ABSTRACT The aims of this research were 1) to find out the social caring caracter at SMA N Colomadu so far, 2) to find out wheter PMR extracurricular activities could affectively shape the remaining social caring character at SMA N Colomadu, 3) to find out what obstacles PMR faced in forming character social care of students in class XI SMA N Colomadu. This research is a qualitative descriptive research. The location of this research is at SMA N Colomadu. The strategy in this research is a case study. The subject in this research were the deputy pricipal for student affairs, PMR supervisors, and students. The data collection techniques used were interviews, documentation and observation. Data validity testing was carried out using source triangulation and method triangulation. The data in this research were analyzed using qualitative techniques and using an interactive analysis model wich includes data collection, data reduction, data display, and drawing conclusions. The results of the research could be concluded that 1) the form of caring character at SMA N Colomadu could be demonstrated by helping friends who were sick in class, lending stationery to friends who needed it, helping people who had accidents on the road, participating in blood donation activities, and helping friends who were sick during the flag ceremony or onther activities, 2) the effectiveness of PMR extracurricular activities in forming social caring characters at the eleventh-grade studens of SMA N Colomadu was effective. This could be seen in student’s daily libe both inside an outside school. 3) there were several obstacles in the process of implementing PMR activities when forming a social caring character, such as: a) lack of student participation in implementing activities carried out by PMR, b) student’s lack of sensitivity tho the environment around them, c) goverment regulations, d) PMR extracurricular ectivities tend to have few members because it was not an extracurricular activity that students were required to participate in. Keywords: Effectiveness, social Caring Character